CEO inside debt holdings and credit ratings. Issue 1 (April 2023) - Hasan, Mostafa Monzur; Hossain, Ashrafee; Hossain, Takdir
Highlights: We examine the relationship between chief executive officer (CEO) inside debt holdings and credit ratings. Firms with a higher level of inside debt holdings enjoy better credit ratings. This relationship is more pronounced in firms with a poor information environment, a weak monitoring mechanism and powerful CEOs. Overall, credit rating agencies positively evaluate insider debt holdings in assessing the creditworthiness of a firm. Abstract: In this paper we investigate the relationship between chief executive officer (CEO) inside debt holdings (pension benefits and deferred compensation) and long-term credit ratings. We provide evidence that firms with a higher level of inside debt holdings enjoy better credit ratings. Our results are robust to the use of alternative regression estimation and alternative measures of key variables. We employ instrumental variable–based two-stage least squares regression and instrumental variable regression estimation using heteroskedasticity-based instruments to mitigate the endogeneity concern. In addition, we employ propensity-matched sample and entropy balancing estimates to alleviate endogeneity concerns. Our cross-sectional analyses reveal that the relationship between CEO inside debt holdings and credit ratings is more pronounced in firms with a poor information environment, a weak monitoring mechanism, and powerful CEOs. Overall, findings from our study suggest that credit rating agencies evaluate CEO insider debt holdings positively in assessing the creditworthiness of a firm.